If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -1 + 10 = 25 Reorder the terms: -1 + 10 + 3x = 25 Combine like terms: -1 + 10 = 9 9 + 3x = 25 Solving 9 + 3x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 3x = 25 + -9 Combine like terms: 9 + -9 = 0 0 + 3x = 25 + -9 3x = 25 + -9 Combine like terms: 25 + -9 = 16 3x = 16 Divide each side by '3'. x = 5.333333333 Simplifying x = 5.333333333
| 75t-16t^2=0 | | 40y-40=-40y+20 | | 28v-92=5v | | 3(x+8)=x+6 | | -48=7+5x | | 15+(0.50x)=25+(0.25x) | | 4+14=-2(2x-9) | | 7n=95 | | x^4+6x^3-x^2-6X=0 | | x^4+6x^3-x^2-6X=0 | | 3x+1=2x+46 | | n-(-2)=-11 | | (3n-2)5= | | 5z+7+z=-8 | | 5y+9=4y-8+4 | | 3d+8=4+3d-.5 | | 15y+2xy=-30 | | y-(-10)=6 | | 3y+1=24 | | 3-12+b=3b+30 | | 22.2=-11.5x | | 4y+26=49 | | 9t-17=33+5t | | 9y+9-7y=5+y-7 | | 3x+2x=5x | | 102n=0 | | 2(x+2)+2=4x-2(-2+x) | | 8(3t-2)=4(7t-4) | | 9x^2-6x+4= | | -9x+9=0 | | -9-(8-5x)=18 | | 5x+4=2x+2 |